Respuesta :
Answer:
SolutioN :
[tex] \bf \: \star ( - 3x^{2} + 4x) + (2 {x}^{2} - x - 11)[/tex]
[tex] \longrightarrow \bf \: - 3 {x}^{2} + 4x + 2 {x}^{2} - x - 11[/tex]
[tex] \longrightarrow \bf \: - 3 {x}^{2} + 2 {x}^{2} + 4x - x - 11[/tex]
[tex] \longrightarrow \boxed{\bf \: - {x}^{2} + 3x - 11}[/tex]
-------------HappY Learning <3 ----------
Given expression:
[tex](-3x^2+4x)+(2x^2-x-11)[/tex]
To simplify the expression, it is needed to open the parentheses.
[tex]\implies (-3x^2+4x)+(2x^2-x-11)[/tex]
[tex]\implies -3x^2+4x+2x^2-x-11[/tex]
To further simplify the expression, let us combine like terms.
[tex]\implies -3x^2+4x+2x^2-x-11[/tex]
[tex]\implies x^{2} (-3 + 2)+x(4-1)-11[/tex]
Now, simplify the expression as needed.
[tex]\implies x^{2} (-3 + 2)+x(4-1)-11[/tex]
[tex]\implies x^{2} (-1)+x(3)-11[/tex]
Finally, open the parentheses to get the simplified form
[tex]\implies x^{2} (-1)+x(3)-11[/tex]
[tex]\implies \boxed{\bold{-x^{2} +3x-11}}[/tex]
[tex]\text{Therefore, the simplified expression is} \ \boxed{-x^{2} +3x-11}[/tex]